Trinidad, West Indies – Little boy in Carnival costume - Braun, Harry (Harry Braun, Hoboken,New Jersey, 2009)
A little boy in a fancy Indian Carnival costume. The postcard is addressed to Mr. and Mrs. Wilson Dallas of Marion, Ohio and affixed to the postcard is a 12 cents Trinidad and Tobago postage stamp.
Colour: Coloured; Style: Portrait; Other: Unbordered, Divided
Keywords: Trinidad and Tobago; Postcards; Carnival; Carnival costumes; 1965; Boys